2016
DOI: 10.1182/blood-2016-03-707844
|View full text |Cite
|
Sign up to set email alerts
|

Inverse agonism at the P2Y12 receptor and ENT1 transporter blockade contribute to platelet inhibition by ticagrelor

Abstract: Key Points• Ticagrelor acts as an inverse agonist at the P2Y 12 R, inhibiting basal agonistindependent signaling. • Ticagrelor inhibits the adenosine transporter ENT1 not only on erythrocytes, but on platelets too.Ticagrelor is a potent antagonist of the P2Y 12 receptor (P2Y 12 R) and consequently an inhibitor of platelet activity effective in the treatment of atherothrombosis. Here, we sought to further characterize its molecular mechanism of action. Initial studies showed that ticagrelor promoted a greater i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 56 publications
6
52
0
1
Order By: Relevance
“…Inhibition of the ADP response was approximately 80% at the highest concentrations of PSB‐0739 tested. Several studies have suggested that ticagrelor produces cardiovascular benefit through a pleiotropic inhibition of the equilibrative nucleoside transporter 1 (ENT‐1) (Aungraheeta et al ., ), and a consequent elevation in extracellular adenosine. To rule out this mechanism of action in THP‐1 cells, we inhibited ENT‐1 using 3 μM 6‐ S ‐[(4‐nitrophenyl)methyl]‐6‐thioinosine (NBMPR), but observed no effect on ADP‐evoked Ca 2+ responses (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of the ADP response was approximately 80% at the highest concentrations of PSB‐0739 tested. Several studies have suggested that ticagrelor produces cardiovascular benefit through a pleiotropic inhibition of the equilibrative nucleoside transporter 1 (ENT‐1) (Aungraheeta et al ., ), and a consequent elevation in extracellular adenosine. To rule out this mechanism of action in THP‐1 cells, we inhibited ENT‐1 using 3 μM 6‐ S ‐[(4‐nitrophenyl)methyl]‐6‐thioinosine (NBMPR), but observed no effect on ADP‐evoked Ca 2+ responses (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…D and E). The observation that the addition of the P2Y 12 receptor antagonist AR‐C66096 enhanced VASP phosphorylation even in the presence of ADP could be explained by the Gi‐independent cAMP increase or inverse agonism by cangrelor or ticagrelor including AR‐C66096 …”
Section: Discussionmentioning
confidence: 99%
“…The observation that the addition of the P2Y 12 receptor antagonist AR-C66096 enhanced VASP phosphorylation even in the presence of ADP could be explained by the Giindependent cAMP increase or inverse agonism by cangrelor or ticagrelor including AR-C66096. 15,16 Akt is independently phosphorylated at Ser473 by mammalian target of rapamycin complex-2 and Thr308 by 3-phosphoinositide-dependent protein kinase-1, respectively. 17,18 Each phosphorylation plays a different role in Akt-mediated signal transduction of human platelets: p-Akt Ser473 mediates proline-rich Akt1 substrate of 40 kDa phosphorylation but is not essential for the aggregation response, while p-Akt Thr308 mediates glycogen synthase kinase 3b phosphorylation and plays an important role in the PLT functional response.…”
Section: Discussionmentioning
confidence: 99%
“…Competitive P2Y 12 receptor antagonists include the nucleotide derivatives cangrelor ( 35 , AR‐C69931MX, N 6 ‐(2‐methylthioethyl)‐2‐(3,3,3‐trifluoropropylthio)‐β,γ‐dichloromethylene‐ATP) and AR‐C67085 (2‐propylthio‐β,γ‐dichloromethylene‐D‐ATP, 28 ; Ingall et al, 1999) as well as nucleoside derivatives such as the orally active ticagrelor ( 36 , AZD6140, Springthorpe et al, 2007; Hoffmann et al, 2009; Hoffmann et al, 2014). Ticagrelor has been reported to act as an inverse agonist under some experimental conditions (Aungraheeta et al, 2016; Garcia et al, 2019). A series of novel analogues of Ap 4 A blocks P2Y 12 receptors at nanomolar concentrations; one of the most potent derivatives was compound 37 (Yanachkov et al, 2016).…”
Section: Selective Ligand Tools To Study P2y Receptorsmentioning
confidence: 99%